'Conversion of the Barbarians' [Huahu ] Discourse as Proto Han Nationalism. (October 2014) - Raz, Gil
In the early medieval period, many Chinese viewed the growing popularity of Buddhism, and the rapid integration of Buddhism into Chinese religious life, as a challenge to their own civilisation. A major aspect of the resistance to the growing dominance of Buddhism was a discourse known as the 'conversion of the barbarians'. This basic narrative of this discourse claimed that Laozi had journeyed west to India where he either became the Buddha or taught the Buddha. This discourse, which was elaborated in several Daoist texts into complex cosmological and mytho-historical narratives thus asserted the primacy of Daoism and relegated Buddhism to a secondary teaching, inferior to Daoism, suitable for 'barbarians' but not for Chinese.  This article discusses the development of this discourse, focusing on texts written by Daoists during the fifth century when this discourse was particularly vehement. In this article I will show that this discourse was not merely resistant to Buddhism, but was also critical of various Daoist groups that had accepted Buddhist ideas and practices. Significantly, this discourse associated Daoism with the essence of Chinese civilisation, rather than as a distinct teaching.